Factors related to recycling plastic packaging in Finland's new waste management scheme. (15th July 2021) - Reijonen, Helen; Bellman, Steven; Murphy, Jamie; Kokkonen, Henna
Highlights: Plastic packaging can be recycled more effectively, economically and environmentally. Source separation in households is key to improve recycling plastic packaging. Environmental concern and convenience are positively related with recycling. Ease of gaining information has negative relationship with recycling behaviour. There is a need for tailoring recycling information content and channels. Abstract: Plastic packaging exemplifies recycling's potential; 95 percent of plastic's material use vanishes after a short first-use cycle. Yet over half of plastic packaging could be recycled effectively, economically, and in an environmentally sound manner, with individuals and households playing a focal role in raising recycling rates. This paper draws on the theory of planned behaviour (TPB) to identify and examine household plastic sorting and recycling factors in Finland's new recycling scheme. The results of a regression analysis generally support existing research, except paradoxically, the easier it was to obtain recycling information the less people recycled. TPB's attitude (environmental concerns) and perceived behavioural control factors (low behavioural costs, and dealing with waste) showed significant positive relationships with Finnish recycling behaviour; the subjective norm (social norms) had an insignificant relationship. Age, living quarters, the time spent recycling, the distance to collection points, and the willingness to improve also related significantly to diligent plastic waste sorting. In addition to re-examining the information type and delivery, the significant role of costs and facilitating conditions offer intervention possibilities to support households to recycle more plastic packaging.